2017
DOI: 10.1590/1983-40632016v4745093
|View full text |Cite
|
Sign up to set email alerts
|

Elicitors on the control of anthracnose and post-harvest quality in papaya fruits1

Abstract: Papaya is one of the most grown and consumed fruits in the world. However, post-harvest diseases are responsible for more than 50 % of losses, including anthracnose, caused by Colletotrichum gloesporioides, which promotes necrotic and rounded lesions and reduces fruit quality. Alternative products have been widely investigated in the control of pathogens. This study aimed at evaluating the efficiency of elicitors in the control of anthracnose, as well as their effect on post-harvest quality, in papaya fruits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The association of control methods is needed to reduce the extent of fruit rots, and to reduce the number of rotten fruits (MAHAJAN et al, 2014). Papaya treatments here presented in combination with phosphites (AMARAL et al, 2017), hot water (AYÓN-REYNA et al, 2017) and radiation (MAHAJAN et al, 2014) might exclude disease, which is an important requirement for papaya fruit commercialization (DEMARTELAERE et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The association of control methods is needed to reduce the extent of fruit rots, and to reduce the number of rotten fruits (MAHAJAN et al, 2014). Papaya treatments here presented in combination with phosphites (AMARAL et al, 2017), hot water (AYÓN-REYNA et al, 2017) and radiation (MAHAJAN et al, 2014) might exclude disease, which is an important requirement for papaya fruit commercialization (DEMARTELAERE et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of the 'Fugi' cultivar maintained the levels of total SS and firmness and promoted a reduction in fruit acidity (Sautter et al, 2008). Demartelaere et al (2017) reported that the application of potassium phosphite (150 mL ha -1 ) did not affect the physicochemical characteristics of papaya fruits regarding pH, SS, TA, and the SS/TA ratio after 12 days of storage. Amaral et al (2017) evaluated the physicochemical characteristics of Sunrise Solo papayas treated with different phosphites (potassium, calcium, calcium and boron, ammonium) and doses (0.3, 0.6, 0.9, 1.25, and 1.5 g L -1 ) and inoculated with Lasiodiplodia theobromae.…”
Section: Effects Of the Alternative Products On The Physical-chemicalmentioning
confidence: 99%
“…In this study, all phosphite doses tested (0.1%, 0.2%, 0.3%, and 0.4%) were efficient in reducing the diameter and growth rate of anthracnose lesions in fruits, as well as the area under the disease progression curve. The application of potassium phosphite in papaya also promoted the reduction of anthracnose lesions in fruits inoculated with C. gloeosporioides when using the dosages of 1.5 mL L -1(Lopes, 2008) and 150 mL ha -1(Demartelaere et al, 2017).Ferraz et al (2016) observed a reduction in the diameter of anthracnose lesions in guavas obtained from conventional and organic cultivation systems, treated with potassium phosphite, and inoculated with C. gloeosporioides at all tested doses (0.5, 1.0, 1.5, and 2.0 mL L -1 ) Amaral et al (2017). evaluated other phosphites (calcium, calcium and boron, and ammonium) in addition to potassium phosphite associated with a modified atmosphere, which was effective in reducing the severity of papaya pod rot caused by the fungus Lasiodiplodia theobromae Alexandre et al (2014).…”
mentioning
confidence: 99%
“…NABCONS (2022) in their study conducted in five districts in three states covering three agroclimatic zones of India, reported postharvest losses of 6.59% in papaya at all levels of farm and market operations. In particular, the volumes of postharvest losses from fungal diseases are often estimated at more than 50% of production (Demartelaere et al, 2017). The three major postharvest diseases reducing shelf life of papaya are anthracnose ( Colletotrichum gloeosporioides ), Rhizopus rot ( Rhizopus stolonifer ), and stem‐end rot (a fungal complex consisting of Phoma caricae‐papayae , Lasiodiplodia theobromae , Fusarium solani , and Alternaria alternata ) (Chowdhury et al, 2014).…”
Section: Introductionmentioning
confidence: 99%